Distribution of Pelagic Fish Species in the Java Sea From Remote Sensing Data - Wijopriono (2006)
Pelagic fishery in the Java Sea is multi-species and dominated by a community of small pelagic species. This study attempted to employ different sources of data in order to determine the distribution of pelagic fish species and to estimate their environmental preferences. Catch per unit effort (CPUE), hydro-acoustic, satellite derived sea surface temperature (SST) and chlorophyll-a data as well as oceanographic in sifu measurements data were used to achieve these objectives. CPUE data were collected from commercial fishing records available at the fishing port of Pekalongan, the main pelagic fish landing centre in the north coast of Java Hydro-acoustic and oceanographic in situ measurements data were collected from hydro-acoustic survey carried out during September-October 2002, while the data of satellite &rived SST of AVHRR-NOAA and chlorophyll-a derived fiom SeaWiFS were collected from the HRPT (High Resolution Picture Transmission) ground receiving station at BPPT (Assessment and Application of Technology Board), Jakarta, and GSFC-NASA (Goddard Space and Flight Center of the National Aeronautics and Space Administration). Correlation analysis, cluster analysis, PCA, spatial analysis and GIs technique were employed in determining abundance and density distribution of pelagic fish species. Spatial analysis and GIs technique together with GLM were also applied in building the fishery-environment dependent model in order to estimate the environmental preferences of the fishes. Results of the study showed that the Java Sea water was seasonally occupied by oceanic water of the Indonesian Throughflow (ITF). The influence of the ITF was most pronounced in the southeast monsoon when the currents in the Java Sea flow towards the west. The influence is minimum in the northwest monsoon when the currents flow towards the east. The sea has a great thermal stability with a monthly SST average of 28.9 OC and the difference between maximum and minimum (gradient) of 2.0-3.5 OC. The abundance of phytoplankton tends to increase towards the west and towards the coastal areas off north coast of Java, south coast of Kalimantan, and around the small islands spreading over the Java Sea. Correlations between physical and biological oceanographic parameters were exhibited. Pelagic fishery resources in the Java Sea have undergone considerable variations in both their seasonal distributions and abundances. They were relatively low during northwest monsoon (December- March), and increased during southeast monsoon (June-September), with a peak at the end of the monsoon. Abundance of the resources was mostly driven by fluctuations in the abundance of one dominant species, SardineIIa spp in the inshore and Decapterus spp in the offshore. The two species make up the average of 36% and 32% of the total CPUE, respectively. GLM model gave evidence that the pelagic fish species have a tolerance limit of temperature of up to 28.5 OC, and below this temperature limit they show a positive trend of relationships with chlorophyll-a concentrations. The model also revealed that oceanographic variables (SST and chlorophyll-a concentrations) contriiuted 54% to the total variance explained by the GLM predictors, confirming the relative importance of these variables in predicting m u s bvmar~rw r pelagic fish catch However, relationship between sea surface temperature ana chlorophyll-a concentrations was weak The GIs model has demonstrated its capability in delineating spatial patterns of fish density in relation to the environmental variables, especially zooplankton, which was not covered in the GLM model.